Altering physical properties of pharmaceutical co-crystals in a systematic manner - Aakeröy, Christer B.; Forbes, Safiyyah; Desper, John (My University, 2014)
Systematic structure-property studies on a series of co-crystals of potential cancer drugs with aliphatic dicarboxylic acids were undertaken. This study reveals that systematic changes to the molecular nature of the co-crystallizing agent combined with control over the way individual building blocks are organized within the crystalline lattice makes it possible to establish predictable links between molecular structure and macroscopic physical properties, such as melting behaviour and aqueous solubility. However, it is not possible to find any notable correlation between physical properties-chemical compositions in the absence of structural consistency.
Keywords: Co-crystals; Cancer drugs; Molecular structure